Changing Risk Perception of Women Investors: An Empirical Study - Paramashivaiah, P.; Puttaswamy,; S. K., Ramya (Indian Journal of Finance, 2014)
Since time immemorial, women have great propensity to save and invest. If not completely, to a great extent, the socioeconomic status of women has been growing in the positive direction. Obviously, their investment decisions and risk perceptions are also changing positively. Unlike previous studies, the present research aims at understanding the risk perceptions of women exclusively. The main aim of the study is to quantify the risk appetite score of women grouped on various socio-demographic bases. The study is based on the sample survey of 120 women in Mysore city. A questionnaire comprising of a 14-item financial risk-tolerance scale developed by Grable and Lytton (1998) (but slightly modified) was used. Risk appetite score was assigned to each respondent on a 5- point Likert summated scale. The respondents were grouped on the basis of the obtained score. The results show that two-thirds of the respondents were above the average score of risk tolerance. Correlation between investment objective and occupation shows a slightly negative relationship. Correlation between risk appetite score and various independent variables allowed us to have a regression model. The regression model suggests that there is a negative influence of age of women on their risk tolerance levels, a finding which is supported by many studies. Only age and education had a positive influence on the risk appetite of women. The study has great implications for the government and investment industry in framing various policies.